Teoria vygotskiana e educação: o que falam desta relação os docentes das universidades de Fortaleza? - Araújo, Claúdio Romero Pereira de (2007)
This study sought to investigate how professors on Psychology and Education courses at universities in the city of Fortaleza see and understand the contribution of Vygotskyan theory to education. The study was base don a qualitative model for research in psychology, with adoption of the theoretical-methodological framework of discoursive practices and production of meaning, according to the proposal by the research group coordinated by Mary Jane P. Spink. The theoretical framework of the research used was that of the historical-cultural Psychological approach of L.S. Vygotsky. The study was undertaken by means of twelve interviews with professors from Fortaleza universities (UFC, UECE and UNIFOR) teaching on Psychology and Education courses, and encompassed the categories of analysis: the meaning of Vygotsky’s theory and its contribution; concepts attributed considered important for general theory and for education; the design of policy for education base don Vygotskyan theory. After analysis of the information obtained, not only was the theory found to be relevant for education, but its entire theoretical construction founded in historic dialectical materialism, consolidating a new concept of the psyche. In this sense, the concepts related to higher psychological processes were emphasized, such as mediation, internalization, Proximal Development Zone (PDZ) and formation of concepts. There was also evidence of the understanding that the theory could be though of in political terms, both in the sense of conception social participation, as well as the feasibility of being used for elaboration of political-pedagogical policy, in addition to the prospect of change and social transformation similar to those of Marxism